PELAKSANAAN KONSOLIDASI TANAH PERKOTAAN UNTUK PEMBANGUNAN JALAN BY PASS DI KOTA BUKITTINGGI - Ana Ramadhona (JCH (Jurnal Cendekia Hukum), 2017)
The increasing price of urban land causes the government difficulty in providing land for development. The status of land tenure will be more legal with the certificate as proof of ownership and ownership of land rights. Presidential Regulation no. 65 year 2006 stated that the procurement of land for the implementation of development for public interest by the government carried out by way of disposal or surrender of land rights. Article 18 of the UUPA explains that the revocation of a person's right to the land owned by the government shall only be exercised if the land is used for the common good including the interests of the nation and the state and the common interest of the people, the rights of the land may be revoked, compensating feasible as regulated by law. This study aims to find out how the implementation of land consolidation for the construction of By Pass in Bukittinggi City. To find out the obstacles faced by the local government of Bukittinggi city in the settlement. This research uses sociological juridical method, primary data in research is interview to informant and second data is library materials. The results show that the implementation of land consolidation of By Pass of Bukittinggi city has not been implemented maximally because the community has not fully understand the purpose and objectives of the implementation of land consolidation so that the people do not wholeheartedly implement it. Constraints faced in the completion of land consolidation for by-pass included the lack of public knowledge about land consolidation, the objections of some communities in handing over their consolidated land to the government and Most of the consolidated lands are customary soils together so it is a bit difficult in decision maker.